Pola Asuh di Panti Asuhan Nurul Hikmah Padang - Erni Gusniwar; Rengga Satria (An-Nuha, 2022)
Parenting is a technique used by parents or caregivers to help and enhance the physical and spiritual development of children. Along with the times, there are currently many bad influences that will occur if children do not get parenting or even get the wrong parenting pattern. The purpose of this research is to describe the parenting style at the Nurul Hikmah Orphanage, Padang. This research uses a descriptive approach and qualitative research techniques. The results showed that there were two types of parenting used, namely democratic and authoritarian. Authoritarian parenting is used for elementary school students, authoritarian and democratic parenting is used for junior high school students, and democratic parenting is used for senior high school students.